Efek Anti Inflamasi Ekstrak Daun Salam (Syzygium Polyanthum) - Widiyanto, Bagas; Sampurna, Sampurna; Rizki Dewinda Putri, Cantika; Adiba Aysar, Nisrina; Brave Sinatrya, Muhamad (Jurnal sosial dan sains, 2025)
Inflammation or inflammation is characterized by increased levels of pro-inflammatory mediators such as IL6, IL1, TNF- and CRP proteins in the blood. One of the mechanisms is through the activation of TLR-4 and NF-κB. Natural remedies have developed, one of which is using bay leaves (Syzygium polyanthum). Bay leaves contain flavonoids, tannins, and saponins that have the potential to be anti-inflammatory. This study aimed to determine the effect of bay leaf extract on IL-6, IL-1, TNF- and CRP protein levels in male white rats of wistar strain induced by 1% carrageenan. Methods: An experimental type of research with a "post test only control group design" design with a research sample of 24 male white rats of the wistar strain, divided into 4 groups randomly. The healthy control group (Knormal), the sick group (Kneg) with 1% carrageenan induction, treatment 1 (K1) was given bay leaf extract 100mg/kgBB, treatment 2 (K2) was given bay leaf extract 200 mg/kgBB. After that, IL-6, IL-1, TNF- and CRP protein levels were checked using ELISA. The data was analyzed using the One Way Anova test followed by the Post Hoc LSD test. Results: The treatment group, namely the administration of bay leaf extract at doses of 100 mg/kgBB (K1) and 200 mg/kgBB (K2), was lower than Kneg and significantly different (p<0.05) in all experimental parameters. The average levels of IL-6, IL-1, TNF- , CRP in the K2 group were lower than in the K1 group. Based on the data above, the dose of bay leaf extract of 200 mgKgBB has better potential as an anti-inflammatory. Conclusion: bay leaf extract has an effect on IL-6, IL-1, TNF-, CRP levels